THE IMPACT OF PEDIATRIC GASTROINTESTINAL AND LIVER DISEASE ON PATIENTS' QUALITY OF LIFE: A SYSTEMATIC REVIEW - M. Hadi, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Aim: Identifies and evaluates all studies and instruments devised to measure quality of life (QOL) in children with gastrointestinal or hepatic diseases.Methods: Using MEDLINE, EMBASE, CINAHL, and PsycINFO, pertinent articles published by the end of 2005 were identified through a search of the literature. These were examined by the two authors, and data were extracted using a standardized form. Articles were excluded if no attempt was made to measure QOL, if they did not pertain to minors 17 years of age, if they did not pertain to gastrointestinal or liver diseases, or if they were reviews. Identified quality of life instruments were evaluated based on proposed criteria.Results: Following the first search, a total of 2379 publications were located; however, following the exclusion of 2309, only 70 research were considered for inclusion. These were classified as having one of the following conditions: inflammatory liver disease, numbering seven. These studies discuss the effects that bowel disease, with a sample size of n = 17, cystic fibrosis, with a sample size of n = 20, and surgery, with a sample size of n = 15, have on the quality of life of children who are afflicted with these conditions. Only five of these condition-specific quality of life instruments and one general instrument with a chronic disease module were found to meet the specified quality standards; hence, only five of these instruments may be recommended for use in the future.Conclusion: Chronic gastrointestinal and liver illnesses can severely impact QOL for patients and their families. Several disease-specific paediatric QOL tools have been validated. Clinical practice and treatment evaluation should include quality of life. Research should focus on improving QOL in seriously handicapped youngsters.